ACCURACY OF ULTRASOUND VERSUS CLINICAL FETAL WEIGHT ESTIMATION AT TERM WITH ACTUAL BIRTH WEIGHT IN KENYATTA NATIONAL HOSPITAL - Wanjaria, Dr. Daniel K.; Kamau, Prof. Koigi (European Journal of Health Sciences, 2022)
Purpose: The purpose of this study was to correlate fetal weight estimation by ultrasound and clinical methods with actual birth weight in KNH. Methodology: This is a prospective comparative study. The design was suitable because it enabled comparison of the predictive value, sensitivity and specificity in estimating fetal weight which is known after birth. Study area was KNH Obstetric wards. The study population was all pregnant women admitted to obstetric wards for elective caesarean delivery and study period was February -March 2016. Data was analysed using SPSS version 20. Categorical variables were presented as proportions in tables and graphs, bars or pie charts). Continuous variable were summarized as means or medians and presented in table form. Results: The findings show that the correlation between actual weight and Ultra Sound estimated weight was significant (r=0.65, p<0.000). The findings further showed that the proportion of Ultra Sound methods estimations within 10% of the actual birth weight was 44% of the overall weights. Clinical methods estimations within 10% of the actual birth weight were 47% of the overall weights. The mean difference between actual birth weights and ultra sound estimated weights were statistically insignificantThe findings revealed that the correlation between actual weight and clinical methods estimated weight was stronger (r=0.79, p<0.000) as compared to the correlation between actual weight and Ultra Sound estimated weight (r=0.65, p<0.000). Unique contribution to theory, practice and policy: The finding of this study may influence further studies and decision on estimation of fetal weight. If clinical estimation is equal or same as ultrasound estimation then it can be recommended that all mothers undergo this instead of ultrasound for estimation of fetal weight. The results may be shared with the University of Nairobi, Kenyatta National Hospital and the Ministry of Health and any policy change resulting from this can be rolled down to counties.